Mehr Beschäftigung mittels weniger Kündigungsschutz?: ökonomische Analyse der Vereinbarungen des Koalitionsvertrages vom 11.11.2005 - Eva Bamberger; Andreas Bielig (Technische Universität Ilmenau, Institut für Volkswirtschaftslehre, 2006)
Rules of employment protection installed by legislation or wage agreements should enhance the failures of the labour market mechanism, for instance to stabilize the demand for labour force over several time periods. Fluctuation of human capital is mostly connected with costs for both parties of the labour market. The raising of one kind of fluctuation tax as done by employment protection rules intends to minimise these negative externalities but has also the effect of establishing barriers against the generation of additional employment by the enterprises. The coalition agreement of the german government from 11.11.2005 extends the waiting period for employment protection intending a stimulation of incentives for more employment. The article analyzes the economic implications of this political driven approach and indicates the small probability of succeeding in comparison with the ambitious aims set by the german governmental policy.
Keywords: 330